The Landscape of Repetitive Elements in the Refined Genome of Chilli Anthracnose Fungus Colletotrichum truncatum - Rao, Soumya; Sharda, Saphy; Oddi, Vineesha; Nandineni, Madhusudan R. (Frontiers in Microbiology, 2018)
The ascomycete fungus Colletotrichum truncatum is a major phytopathogen with a broad host range which causes anthracnose disease of chilli. The genome sequencing of this fungus led to the discovery of functional categories of genes that may play important roles in fungal pathogenicity. However, the presence of gaps in C. truncatum draft assembly prevented the accurate prediction of repetitive elements, which are the key players to determine the genome architecture and drive evolution and host adaptation. We re-sequenced its genome using single-molecule real-time (SMRT) sequencing technology to obtain a refined assembly with lesser and smaller gaps and ambiguities. This enabled us to study its genome architecture by characterizing the repetitive sequences like transposable elements (TEs) and simple sequence repeats (SSRs), which constituted 4.9% and 0.38% of the assembled genome, respectively. The comparative analysis among different Colletotrichum species revealed the extensive repeat rich regions, dominated by Gypsy superfamily of long terminal repeats (LTRs), and the differential composition of SSRs in their genomes. Our study revealed a recent burst of LTR amplification in C. truncatum, C. higginsianum and C. scovillei. TEs in C. truncatum were significantly associated with secretome, effectors and genes in secondary metabolism clusters. Some of the TE families in C. truncatum showed cytosine to thymine transitions indicative of repeat-induced point mutation (RIP). C. orbiculare and C. graminicola showed strong signatures of RIP across their genomes and “two-speed” genomes with extensive AT-rich and gene-sparse regions. Comparative genomic analyses of Colletotrichum species provided an insight into the species-specific SSR profiles. The SSRs in the coding and non-coding regions of the genome revealed the composition of trinucleotide repeat motifs in exons with potential to alter the translated protein structure through amino acid repeats. This is the first genome-wide study of TEs and SSRs in C. truncatum and their comparative analysis with six other Colletotrichum species, which would serve as a useful resource for future research to get insights into the potential role of TEs in genome expansion and evolution of Colletotrichum fungi and for development of SSR-based molecular markers for population genomic studies.